Strategy map of servitization - Rabetino, Rodrico; Kohtamäki, Marko; Gebauer, Heiko (Elsevier, 2017)
By representing the servitization of three leading corporations via a strategy map, this multiple-case study discusses how the strategic logic of servitization can be explained by linking the key practices adopted by manufacturers to support critical processes while shifting their focus to project-based customer solutions. The results draw on data collected from solution providers operating in the metal and machinery industries headquartered in Finland. By examining the strategic actions, tools, and processes behind the implementation of servitization, this study extends recent debates on the service-based business models of manufacturing companies. For servitization theory, this study develops a strategy map for a solution provider. For manufacturing firms, this study provides a framework and a tool for benchmarking, developing and implementing a strategy while mitigating the processes of long-term value creation and appropriation.
Keywords: servitization; strategy map; manufacturing; business model; product-service systems; fi=Johtaminen ja organisaatiot|en=Management and Organization|